Development and Initial Validation of a Harmonised Multi-Jurisdiction Work Injury Compensation Database - Collie, Alex; Di Donato, Michael; Beck, Dianne; Sheehan, Luke R (International Journal of Population Data Science, 2020)
Introduction Nearly one quarter of a million Australian workers experience a work injury annually and make a benefit claim through one of the nation’s eleven workers’ compensation (WC) systems. The total cost to Australian society has most recently been estimated at $61.8 billion or 4.1% of GDP. The disaggregation of legislative responsibility between jurisdictions has contributed to a lack of common data standards, and thus minimal understanding of the efficiency or effectiveness of service provision in the Australian WC sector. Objectives and Approach This project developed a new multi-jurisdictional work disability database including detailed information on work disability duration, health and social care service provision. Service level payment data contained in structured WC insurance claims datasets held by five large WC jurisdictions with >60% coverage of the Australian labour force was collected for all cases of work-related low back pain, fractures and limb soft tissue disease over between 2010 and 2015. Database development involved creation and coding of harmonised service-level indicators for individual episodes of healthcare provision and weekly periods of wage replacement. Results A total of 253,000 cases and 10.7 million service episodes are included in the database. Initial exploratory analyses focused on the frequency, prevalence, timing, intensity and continuity of General Practitioner (GP) services to each of the injury groups. Regression modelling examined occupational, injury, demographic and jurisdictional factors affecting GP service use outcomes. As anticipated, service patterns varied by injury type, age, gender and occupational group. Significant differences in service use between WC jurisdictions were observed. Conclusion / Implications This exploratory study demonstrates the feasibility of developing a population-based service level database for monitoring health service delivery to injured Australian workers. Future studies will examine the impact of jurisdictional policy differences on service delivery, and the relationship between service delivery and outcomes such as disability duration.